I want to find the residue $\displaystyle\frac{\cos (\pi z)}{z^2-1}$ at $z=1$.

The function has two poles, at $-1,1$, both of order $1$. The series expansion for the function gives $\displaystyle\frac{1}{z^2-1}\left(1- \frac{z^2\pi^2}{2!}+O(z^4z\pi^4) \right)$.

(1) Is then Laurent series the following? $$\frac{1}{z^2-1}- \frac{z^2\pi^2}{2!(z^2-1)}+\frac{z^4}{4!(z^2-1)}+\dots$$

(2) How do I find the pole of order $1$ from the Laurent series?

(3) I know that the residue should be given by $\displaystyle\lim_{z \to 1}(z-1)\frac{\cos (\pi z)}{z^2-1}=\frac{1}{z+1}- \frac{z^2\pi^2}{2!(z+1)}+\frac{z^4\pi^4}{4!(z+1)}+\dots=\frac{1}{2}-\frac{\pi^2}{2\cdot2!}+\frac{\pi^4}{2\cdot4!}+\dots$

Is the residue $1/2$? I am not sure of what term in the Laurent series I should pick up to be the residue.

  • $\begingroup$ That's not a Laurent series. A Laurent series is a series in powers of $z-a$ for some $a$. But in your (3), forget the series – just cancel $z-1$, and evaluate. $\endgroup$ – Gerry Myerson Nov 12 '17 at 6:40

You have the function $f(z) = \frac{g(z)}{z^2-1}$, where $g(z)= \cos(\pi z)$ and therefore holomorf. The residue at $z=1$:

Using limits. \begin{align} \text{Res}_{z=1} f(z) =\lim_{z\to 1} (z-1)\frac{g(z)}{(z-1)(z+1)} = \frac{g(1)}{2} = \frac{-1}{2} \end{align} Using Laurent series. You must have powers of $z-1$ in your laurent series: \begin{align} \frac{\cos(\pi z)}{z^2-1} &= \frac{\cos(\pi(z-1) + \pi)}{(z-1)(z+1)} \\& = -\frac{\cos(\pi( z-1))}{(z-1)((z-1)+2)}\\ & = -\frac{1}{2}\frac{\cos(\pi( z-1))}{(z-1)((z-1)/2+1)} \\ &= -\frac{1}{2}\cdot \frac{\cos(\pi(z-1))}{(z-1)} \cdot \sum_{k=0}^\infty (-(z-1))^k \\ &= -\frac{1}{2} (1 + O((z-1)^2) \sum_{k=0}^\infty (-1)^k(z-1)^{k-1}\\ &=-\frac{1}{2} (1 + O((z-1)^2) \cdot ((z-1)^{-1}+O(1))\\ &= -\frac{1}{2} (z-1)^{-1} + O(1) \end{align} We used the geometric series. Now you can see the coefficient of $(z-1)^{-1}$ is $-\frac 1 2 $ and therefore the residue at $z=1$ is $-\frac 1 2 $.


Use the next result: if $g(z)$ is holomorphic at $z_0$ and $h(z)$ has a simple pole at $z_0$, then $Res(gh,z_0)=g(z_0)Res(h,z_0)$. Take $$g(z)=\frac{cos(\pi z)}{z+1}$$ $$h(z)=\frac{1}{z-1}$$ The residue is: $$Res(gh,1)=g(1)Res(h,1)=-\frac{1}{2}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.